Implementasi Model Pembelajaran Osborn Berbasis Assisted Learning untuk Meningkatkan Kemampuan Numerasi Peserta Didik SDN Malangga - Ristanti, Ristanti; Mustakim, Mustakim; Hamna, Hamna (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research is based on the identification of numeracy skills deficiencies among Class IV students at SDN Malangga, particularly in the context of low grades in mathematics subjects. The low numeracy abilities observed in students can be attributed to two key factors: the student factor and the teacher factor. The objective of this research is to enhance the numeracy abilities of fourth-grade students at SDN Malangga through the utilisation of the Assisted Learning Osborn Learning Model. This research is of the action research (PTK) variety, conducted within a classroom setting. The subjects of this study were 10 fourth-grade students at SDN Malangga. The research object is located at Malangga Elementary School, Galang District, Tolitoli Regency. The data collection techniques employed in this study were student observation, teacher observation, and the administration of evaluation tests. Prior to the validation of observations and tests by expert validators and practitioners, it is essential to ascertain the appropriateness of the research instruments employed by the researchers. The research action was conducted in two cycles. The findings of the study demonstrate that the Osborn assisted learning model has the potential to enhance students' mathematical learning outcomes. The research was conducted with a sample of 10 fourth-grade students at SDN Malangga. The students' proficiency in numeracy increased from 60% in Cycle I to 100% in Cycle II, indicating that the Osborn assisted learning model can effectively facilitate the development of students' numeracy abilities.